2019
DOI: 10.1370/afm.2355
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Clinician Adherence to Specialist Advice in Electronic Consultation

Abstract: PURPOSE Electronic consultation (eConsult) services can improve access to specialist advice. Little is known, however, about whether and how often primary care clinicians adhere to the advice they receive. We evaluated how primary care clinicians use recommendations conveyed by specialists via the Champlain BASE (Building Access to Specialists through eConsultation) eConsult service and how eConsult affects clinical management of patients in primary care. METHODS This is a descriptive analysis based on a retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 16 publications
0
11
0
3
Order By: Relevance
“…We screened 181 full-text articles, of which we excluded 108 records after applying exclusion criteria. A total of 72 studies were eligible for data extraction (Figure).…”
Section: Resultsmentioning
confidence: 99%
“…We screened 181 full-text articles, of which we excluded 108 records after applying exclusion criteria. A total of 72 studies were eligible for data extraction (Figure).…”
Section: Resultsmentioning
confidence: 99%
“…As such, we could not determine whether and to what extent PCPs followed specialists' advice, nor examine any follow-up conversations between the PCP and the patient. Though a recent study by our team found that PCPs adhered to specialist advice in 82% of cases (39), the nature of the data nevertheless limits our ability to interpret outcomes. Additional case studies that include patient and PCP follow-up through interviews and access to health administrative data would be illuminating.…”
Section: Discussionmentioning
confidence: 97%
“…Tras una sola consulta no presencial del especialista de Aparato Digestivo sería posible hacer el diagnóstico, pautar un tratamiento e, incluso, fijar una revisión para la misma. Analizadas las e-consultas realizadas en nuestro medio, podemos afirmar que los resultados obtenidos son similares a los descritos en estudios realizados en otros países [19][20][21] . La e-consulta lleva años aplicándose en gran parte del territorio nacional, aunque en cada AS tiene sus particularidades.…”
Section: Comentariounclassified
“…Diversos estudios norteamericanos relativos a la utilidad y satisfacción de la e-consulta objetivan que la mayoría se realizaron al Servicio de Gastroenterología, y entre ellas las relativas a endoscopias 19 . Además, estos estudios analizan los motivos por los que son llevadas a cabo: la mayor parte de las preguntas de los MF son relativas a cuestiones diagnósticas 20,21 . No obstante, carecemos de estudios que analicen la e-consulta en nuestro medio en relación con la utilidad, satisfacción o consumo de recursos.…”
Section: Introductionunclassified